My Sassy girl
Based on a series of true stories by Ho-Sik Kim on the Internet. It describes his relationship with his girlfriend. It describes the meeting of Kyun-woo (Cha) and an unnamed girl, Kyun-wee. He is ashemed in insisting the girl because the other passenger mistakenly think she is his girl. Once he helps her, Kyun-woo develops a deep sense of responsibility for her which enables him to tolerate (somehow) the girl's abuses.